CRIMINOLOGICAL ASPECTS OF FAMILY RELATIONS - Kipāne, Aldona (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The dynamic variability of the modern world determines not only the need to adapt but also the ability to preserve and maintain the values of separate culture. Over the centuries, family is considered to be one of the core values. Family interaction with the society is undeniable. The family is the foundation of any society and the future of the state. Today's new socio-economic situation has an impact on the emotional atmosphere, quality and relationships within the family. Criminological research in family relationships is a complex problem, its environment and circumstances are an important factor in the individual's socialization. The role of the family is equally important both in the process of proper behavioural shaping and in the production of directed behaviour. The article provides an insight into the content of the studies of family criminology.The aim of the article is to describe the criminological framework of family relations based on special literature, research and practice showing the framework of family criminology. Theoretical guidelines, special literature, views and opinions of Latvian and foreign specialists have been analysed in order to assess the criminological aspects of the phenomenon.The author concludes that the knowledge of family criminology is useful, effective, concrete and practically feasible for the criminological studies of the family institute. This approach has a multi-sectoral nature.